Constituição, capitalismo, sociedade: uma reconstrução das contribuições marxistas no Brasil pós-Constituição de 1988 para uma crítica do constitucionalismo - João Pedro Lopes Fernandes (2024)
I will work with the fragments of a Marxist constitutional theory among Brazilian authors in the period after the Constitution of the Republic of 1988. After a longer crisis of Marxism, the Marxist tradition renews its explanatory potential with MEGA-2 publications, especially in Latin America. The field of "law and marxism" in Brazil resurfaced after the 2000s, and the differences between approaches that contribute to the understanding of the Brazilian crisis in the Marxist perspective were made explicit. In this work, I deal specifically with the formulations that used concepts, categories or faced problems typical of the Theory of Constitution. Added to this lack is the absence of a comprehensive mapping of the field. I face the problem of the existence (or not) of a Marxist theory of the constitution in Brazil after the 1988 Constitution. In the framework of a Theory of the Constitution as Theory of Society, I use the Habermasian reconstructive method, while using the categorical reconstruction as a way of exposing the results. Thus, I reconstruct the fragments of four distinct approaches to Constitutional Theories proposed by Marxists. After reconstructing in categorical constellations the first three paradigmatic approaches of a Marxist Theory of Constitution, I explain the Hegelian-Marxist tradition developed in the Faculty of Law of UFMG, I conclude that this tradition differs from the approaches of the traditional Constitution Theory.